Preparation method of nickel-ruthenium bimetal loaded defective indium oxide material for photocatalytic carbon dioxide reduction

By preparing nickel-ruthenium bimetallic supported indium oxide rich in oxygen vacancies, a gradient functional composite structure was constructed, which solved the problem of uneven distribution of active sites in diatomic catalysts and achieved highly efficient photocatalytic reduction of CO2 to CO, with significantly improved generation rate and selectivity.

CN121422987APending Publication Date: 2026-01-30EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511633493.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-10
Publication Date
2026-01-30

AI Technical Summary

Technical Problem

Existing technologies struggle to effectively construct biatomic active sites with uniform spacing, limiting the synergistic effect of biatomic catalysts in photothermal CO2 reduction and resulting in insufficient reaction efficiency and selectivity.

Method used

Indium oxide material rich in oxygen vacancies supported by nickel-ruthenium bimetallic sites is used to enhance CO2 adsorption by modulating the electronic structure and constructing a composite structure with gradient functions. Oxygen vacancies promote the capture and transport of photogenerated electrons, and Ru nanoparticles provide an optimized proton transport pathway. This achieves the synergistic effect of the bimetallic sites, reduces the intermediate state energy barrier, and promotes the selective generation of CO.

Benefits of technology

The process of highly efficient photocatalytic reduction of CO2 to CO was achieved, with a CO generation rate of 892.84 μmol g-1h-1 and a selectivity of 77.1%, which significantly improved the stability and selectivity of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a catalyst for photocatalytic reduction of CO2 into CO by using a nickel-ruthenium bimetal-loaded oxygen vacancy-rich indium oxide semiconductor material. Firstly, indium nitrate hydrate and nickel nitrate hexahydrate are used as substrates, a high-temperature and high-pressure hydrothermal reaction is utilized, a nickel source is added into a precursor, oxygen vacancies are introduced through calcination of a muffle furnace, a nickel-loaded oxygen-vacancy-rich indium oxide material is prepared, and then metal ruthenium is loaded to the surface of the nickel-loaded oxygen-vacancy-rich indium oxide material through a photodeposition method. A series of characterization proves that the catalyst is black powder, has excellent absorption in a full visible spectrum section of 200-1000 nm and excellent photo-thermal catalytic activity, and shows excellent activity when being applied to a reaction for photocatalytic reduction of CO2 into CO, the generation rate of CO can reach 892.84 [mu] mol g <-1 > h <-1 >, and the selectivity is 77.1%.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of advanced nanomaterials and energy conversion, and particularly relates to a preparation method of a nickel-ruthenium bimetallic loaded oxygen vacancy rich indium oxide material for a photocatalytic carbon dioxide reduction to carbon monoxide reaction. BACKGROUND

[0002] With the development of global economy and society, energy demand continues to rise. At present, global energy consumption is still highly dependent on coal, oil and natural gas and other non-renewable fossil fuels. However, fossil fuels have limited reserves, and their large-scale combustion and utilization have led to serious environmental problems, especially the massive emission of greenhouse gases such as carbon dioxide (CO2), which has triggered a series of crises such as global climate warming, sea level rise and ecological system imbalance. Therefore, developing clean and renewable new energy systems to replace traditional fossil energy has become a top priority to solve energy and environmental problems.

[0003] In order to balance energy efficiency and reaction rate, photothermal synergistic catalysis strategy emerges as the times require. This technology uses photothermal materials to achieve full-band absorption of the solar spectrum, generating local high temperature at the catalytically active site, thereby efficiently driving the CO2 reduction reaction. Photothermal catalysis not only effectively reduces external energy input and waste, but also achieves high solar energy utilization rate, CO2 conversion rate and product selectivity, showing broad application prospects.

[0004] Rational design of catalysts is the core to improve the performance of photothermal catalysis. As a new system, diatomic catalysts can effectively regulate the coordination environment and electronic structure of active sites by introducing a second homonuclear or heteronuclear metal atom. Compared with single-atom catalysts, diatomic catalysts not only provide multiple adsorption and activation sites, maintaining high atomic utilization, but also can catalyze reaction steps that single-atom sites cannot complete through the synergistic effect between two atoms, thereby significantly improving the overall reaction kinetics. This synergistic effect is particularly important in reactions such as hydrogenation that require active sites.

[0005] Therefore, there is an urgent need in the art to develop a synthetic method capable of precisely constructing a bimetallic active site with uniform spacing to fully exploit the synergistic advantages of bimetallic catalysts in the photocatalytic reduction of CO2, and to promote the development of this technology towards high efficiency and practicality. Based on the above research background, the present application prepared a nickel-ruthenium bimetallic loaded oxygen vacancy rich indium oxide material. On the one hand, the oxygen vacancy rich In2O3 powder changed from yellow to black, realizing full spectrum absorption, greatly enhancing the photo-thermal catalytic effect. On the other hand, there is a strong adjacent synergistic effect between the NiRu bimetallic sites, and this synergistic effect mainly depends on the distance between the NiRu bimetallic sites. As the Ru-to-Ni distance increases, the *H overflow is weaker, and the electron transfer from Ru to Ni site is less. The nickel-ruthenium bimetallic loaded oxygen vacancy rich indium oxide material prepared by the present application realizes the efficient reduction process of photocatalytic reduction of CO2. SUMMARY

[0006] The key problem solved by the present application is to construct a photocatalytic material with excellent photocatalytic activity for the reduction of CO2 to CO, and to further study the mechanism of activity change.

[0007] The present application provides a preparation scheme of a photocatalytic material with excellent photocatalytic activity for the reduction of CO2 to CO, which can be realized by the following technical scheme:

[0008] A photocatalytic material with excellent photocatalytic activity for the reduction of CO2 to CO is a nickel-ruthenium bimetallic loaded oxygen vacancy rich indium oxide nanomaterial. The nickel-ruthenium bimetallic loading provides a synergistic active site, the loading of nickel enhances the adsorption of carbon dioxide, the loading of ruthenium provides hydrogen overflow, reduces the energy barrier of formic acid intermediate, and the increase of oxygen vacancy greatly increases the light absorption efficiency, thereby exhibiting excellent activity in the photocatalytic reduction of carbon dioxide to carbon monoxide reaction.

[0009] The nickel-ruthenium bimetallic loaded oxygen vacancy rich indium oxide nanomaterial has excellent photocatalytic activity for the reduction of CO2 to CO, and the generation rate of CO can reach 892.84 μmol g -1 h -1 , and the selectivity is 77.1%.

[0010] The method specifically comprises the following steps:

[0011] (1) In a round bottom flask, 0.1 mmol of indium nitrate hydrate and 0.1 mmol of nickel nitrate hexahydrate were dissolved in 50 ml of deionized water. The mixed solution was magnetically stirred at room temperature for 30 min to ensure that the metal salts were fully dissolved and uniformly mixed. 0.1 mol of urea was added to the above clear solution, and the solution was continuously magnetically stirred for 30 min to adjust the alkaline environment. The mixed solution was transferred to a 100 ml polytetrafluoroethylene lined stainless steel high-pressure reaction kettle, which was sealed and placed in a 140℃ air-drying oven for 18 h. After the reaction kettle was naturally cooled to room temperature, it was opened and the precipitate was collected by filtration. The precipitate was washed with deionized water three times to remove residual ions. The washed precipitate was placed in a 70℃ vacuum drying oven overnight to obtain a nickel-loaded indium oxide precursor.

[0012] (2) The product was heat treated and reduced. The precursor powder obtained in the first step was placed in a muffle furnace, which was programmed to heat to 600℃ at a rate of 5℃ / min in an air atmosphere, and calcined at this temperature for 2 h. The calcined powder was transferred to a tube furnace, which was programmed to heat to 350℃ at a rate of 5℃ / min in a 5% H2 / Ar mixed gas atmosphere, and reduced at this temperature for 2 h. The reduced sample was washed with deionized water three times and dried at 70℃ overnight to obtain a nickel-loaded indium oxide carrier with oxygen vacancies.

[0013] (3) 200 mg of the oxygen vacancy nickel-loaded indium oxide carrier prepared in step two was uniformly dispersed in a mixed solution composed of 30 mL of deionized water and 30 mL of ethanol, and ultrasonically treated for 10 min to form a uniform suspension. 1 g / L of ruthenium trichloride solution was added to the suspension. The mixed solution was irradiated with a 300 W xenon lamp for 1 h under continuous magnetic stirring. After the reaction was completed, the solid product was collected by filtration, washed with deionized water three times, and finally dried at 70℃ overnight to obtain the final target catalyst, a nickel-indium bimetallic-loaded indium oxide with oxygen vacancies.

[0014] The amount of indium nitrate hydrate added in step one is 0.1 mmol, and the amount of nickel nitrate hexahydrate added is 0.1 mmol.

[0015] In step three, 1 g / L of ruthenium trichloride solution is added. The advantages of the present application are

[0016] 1. Ni doping of indium oxide (IO) modulates its electronic structure, effectively enhancing CO2 adsorption capacity and promoting photogenerated carrier separation. Further, by introducing a precursor and calcining in a muffle furnace, abundant oxygen vacancies are constructed in the IO, forming defect energy levels, broadening the spectral response range, and optimizing the band structure. Subsequently, Ru nanoparticles with hydrogen spillover effect are loaded via photodeposition, forming bimetallic synergistic catalytic centers with the nickel doping sites. This achieves highly efficient activation and directional conversion of CO2 molecules, overcoming the high dependence of traditional catalysts on noble metals.

[0017] 2. The Ru nanoparticles formed by photodeposition interact strongly with the oxygen-vacancy-rich nickel-doped indium oxide support through interfacial electronic coupling, effectively regulating the electron density of active sites. The adjustable oxygen vacancy concentration and flexible electron transport channels in the support further endow the material with dynamic control capabilities, enhancing the stability and selectivity of the catalyst in the photocatalytic CO2 reduction process.

[0018] 3. The catalyst forms a composite structure with gradient functions during its construction: nickel doping sites enhance CO2 adsorption, oxygen vacancies promote photogenerated electron capture and transport, and Ru nanoparticles provide an optimized proton transport pathway. Active hydrogen species generated at Ru sites migrate to nearby CO2 activation sites through a spillover effect, significantly reducing the intermediate state energy barrier. The synergistic effect of oxygen vacancies and bimetallic sites effectively regulates the reaction pathway, promoting selective CO generation, while simultaneously suppressing side reactions through a dynamic hydrogen transfer mechanism, thereby improving catalytic efficiency and product selectivity. Attached Figure Description

[0019] Figure 1 isNiRu-In2O 3-x A schematic diagram of the preparation process.

[0020] Figure 2 Yes(a)NiRu-In2O 3-x Schematic diagram of the mechanism of CO2 reduction under solar irradiation. (b) X-ray diffraction (XRD) patterns of different catalysts. Figure 2 (a) is a microscopic schematic diagram of CO2 reduction on the catalyst of the present invention. Figure 2 The XRD pattern in (b) illustrates that the present invention is an In₂O rich in oxygen vacancies. 3-x The absence of other peaks indicates that the product is pure.

[0021] Figure 3 It is (ac)In2O 3-x (df)Ni-In2O 3-x (gi)NiRu-In2O 3-x TEM images at different sizes. TEM results show that the loading of nickel and ruthenium does not have a significant impact on the morphology.

[0022] Figure 4 It is In2O 3-x (a) HRTEM (b) SAED (c) Interplanar spacing; Ni-In2O 3-x (d) HRTEM (e) SAED (f) Interplanar spacing; NiRu-In2O 3-x (g)HRTEM(h)SAED(i) interplanar spacing.

[0023] Figure 5 It is In2O 3-x (a) HAADF-STEM (bd) EDS images; Ni-In2O 3-x (e) HAADF-STEM (fh) EDS images; NiRu-In2O 3-x (i) HAADF-STEM and (jl) EDS images. HAADF-STEM shows that nickel and ruthenium are uniformly dispersed.

[0024] Figure 6 These are (a) UV-Vis-NIR spectra of different catalysts, (b) Tauc plot, and (c) Mott-Schottky plot. Figure 6 (a) illustrates the full visible spectrum absorption of the present invention.

[0025] Figure 7 XPS plots of different catalysts: (a) In 3d, (b) O 1s; NiRu-In2O 3-x XPS plots (c) Ni 2p (d) Ru 3d; EPR plots (e) for different catalysts. Figure 7 (b) illustrates the existence of abundant oxygen vacancies. Figure 7 (c) and (d) confirm that NiRu-In2O 3-x The presence of Ni and Ru.

[0026] Figure 8 These are (a) activity data graphs, (bd) selectivity graphs, and (c) NiRu-In2O catalysts. 3-x Four active cycles (d) of contamination testing. (By...) Figure 8 (a) It can be seen that NiRu-In2O 3-x It has the highest CO production rate of 892.84 μmol g. -1 h -1 The CO selectivity was 77.1%.

[0027] Figure 9 The images show (a) transient photocurrent response, (b) impedance diagram, and (c) fluorescence spectrum of different catalysts. The fluorescence spectrum indicates that the presence of NiRu diatoms and oxygen vacancies helps to slow down carrier recombination. Detailed Implementation Plan

[0028] The application will be described in detail below with reference to specific embodiments, but the scope of protection of the application is not limited to these embodiments.

[0029] The application provides a preparation method of a catalyst for a photocatalytic reduction CO2 to CO reaction, and the specific steps are as follows: Example 1

[0030] Preparation of Ni-In2O3

[0031] In a round-bottom flask, 0.1 mmol of indium nitrate hydrate and 0.1 mmol of nickel nitrate hexahydrate were dissolved in 50 ml of deionized water. The mixed solution was magnetically stirred at room temperature for 30 min to ensure that the metal salts were fully dissolved and uniformly mixed. 0.1 mol of urea was added to the above clear solution, and the solution was continuously magnetically stirred for 30 min to adjust the alkaline environment. The mixed solution was transferred to a 100 ml polytetrafluoroethylene-lined stainless steel high-pressure reaction kettle, which was sealed and placed in a 140℃ air-drying oven for reaction for 18 h. After the reaction kettle was naturally cooled to room temperature, it was opened and the obtained precipitate was collected by filtration. The precipitate was washed with deionized water three times to remove residual ions. The washed precipitate was placed in a 70℃ vacuum drying oven and dried overnight to obtain a nickel-loaded indium oxide precursor. Example 2

[0032] Preparation of NiRu-In2O3 3-x

[0033] The above product was heat-treated and reduced. The precursor powder obtained in the first step was placed in a muffle furnace, which was programmed to heat to 600℃ at a rate of 5℃ / min in an air atmosphere, and calcined at this temperature for 2 h. The calcined powder was transferred to a tube furnace, which was programmed to heat to 350℃ at a rate of 5℃ / min in a mixed gas atmosphere of 5% H2 / Ar, and reduced at this temperature for 2 h. The reduced sample was washed with deionized water three times and dried at 70℃ for 12 h to obtain a nickel-loaded indium oxide carrier with oxygen vacancies. Example 3

[0034] Preparation of NiRu-In2O3 3-x

[0035] ​​Take 200 mg of the oxygen vacancy nickel-loaded indium oxide support prepared in step two, uniformly disperse it in a mixed solution composed of 30 mL of deionized water and 30 mL of ethanol, and ultrasonically treat it for 10 min to form a uniform suspension. Add 1 g / L of a ruthenium trichloride solution to the suspension. Irradiate the mixed solution with a 300 W xenon lamp for 1 h under continuous magnetic stirring. After the reaction is completed, filter the solid product, wash it with deionized water three times, and finally dry it at 70 ℃ for 12 h to obtain the final target catalyst, nickel-indium bimetallic atom-loaded indium oxide with oxygen vacancies.

[0036] The photocatalytic material prepared by the above method is a black powder, and when the nickel and ruthenium bimetallic atoms are loaded and have abundant oxygen vacancies, the catalytic activity is best, and the CO generation rate is 892.84 μmol g -1 h -1 , and the CO selectivity is 77.1%. Comparative Example 1

[0037] Preparation of unmodified In2O 3-x

[0038] Dissolve 0.1 mmol of In(NO3)3·xH2O in a certain amount of deionized water, and stir thoroughly for 30 min. Next, add 0.1 mol of urea (CO(NH2)2) to the above solution, adjust the alkaline environment, and mix the solution under stirring for 30 min. Perform a high-temperature and high-pressure hydrothermal reaction at 140 ℃, collect the obtained precipitate by filtration, wash it with deionized water three times, and dry it at 70 ℃ overnight. Then, program the temperature of the dried powder in a muffle furnace to increase at a rate of 5 ℃ / min to 600 ℃, and calcine it for 2 h, wash it with deionized water three times, and dry it at 70 ℃ for 12 h. Experiments and data

[0039] The activity investigation method of the photocatalytic methane dry reforming provided by the present application is as follows:

[0040] ​Laboratory xenon lamp simulation light irradiation activity investigation method: 10 mg of photo-thermal catalyst was mixed into 0.5 ml of deionized water, ultrasonic mixed uniformly, the mixed solution was dropped on high purity quartz fiber filter membrane, and placed in a carbon-free oven for drying. The dried filter membrane was placed in the center of the reaction zone of the quartz support. The total flow rate of the reaction gas CO2 was adjusted to 10 mL·min⁻¹ by a high-precision mass flow controller, which first passed through a flask containing deionized water and then entered the quartz reactor to ensure uniform distribution of the reactants on the surface of the catalyst. The optical system used a 300W xenon lamp light source, and the light intensity was monitored in real time by a light power meter (Thorlabs PM100D). The product analysis used a gas chromatography system (GC 9790II) equipped with a double detector: a thermal conductivity detector (TCD) for detecting H2 and CO2, and a flame ionization detector (FID) for detecting CO and CH4 and other hydrocarbons. All experiments were carried out at normal temperature and pressure.

Claims

1. A material of Ni-Ru bimetallic supported oxygen vacancy-rich indium oxide for photocatalytic reduction of carbon dioxide to carbon monoxide and a method for preparing the same, characterized in that, The method uses hydrated indium nitrate and nickel nitrate hexahydrate as substrates, uses high-temperature and high-pressure hydrothermal reaction, adds nickel source in the precursor, introduces oxygen vacancies by calcining in a muffle furnace, prepares nickel-loaded indium oxide material rich in oxygen vacancies, and then uses photodeposition method to load metal ruthenium.

2. The prepared material is used in the photocatalytic reaction of carbon dioxide to carbon monoxide, and because it has nickel-ruthenium double-metal loading, it provides a synergistic active site, the loading of nickel enhances the adsorption of carbon dioxide, the loading of ruthenium provides hydrogen overflow, reduces the energy barrier of the formic acid intermediate, and the increase of oxygen vacancies greatly increases the light absorption efficiency, thereby exhibiting excellent activity in the photocatalytic reaction of carbon dioxide to carbon monoxide.

3. Specifically includes the following steps: First, in a round-bottom flask, 0.1 mmol of hydrated indium nitrate and 0.1 mmol of nickel nitrate hexahydrate are dissolved in 50 ml of deionized water, the above mixed solution is magnetically stirred at room temperature for 30 min to ensure that the metal salt is fully dissolved and uniformly mixed, 0.1 mol of urea is added to the above clear solution, and the above solution is continuously magnetically stirred for 30 min to adjust the alkaline environment; the mixed solution is transferred to a 100 ml polytetrafluoroethylene-lined stainless steel high-pressure reaction kettle, sealed and placed in a 140℃ air-drying oven for 18 h; after the reaction kettle is naturally cooled to room temperature, it is opened and the obtained precipitate is collected by filtration; the precipitate is washed with deionized water three times to remove residual ions; The washed precipitate is placed in a 70℃ vacuum drying oven overnight to obtain a nickel-loaded indium oxide precursor; Second, the product is heat-treated and reduced, the precursor powder obtained in the first step is placed in a muffle furnace, programmed to 600℃ at a rate of 5℃ / min in an air atmosphere, and calcined at this temperature for 2 h; the calcined powder is transferred to a tube furnace, programmed to 350℃ at a rate of 5℃ / min in a mixed gas atmosphere with a volume ratio of 5% H2 / Ar, and reduced at this temperature for 2 h; the reduced sample is washed with deionized water three times and dried at 70℃ overnight to obtain a nickel-loaded indium oxide carrier with oxygen vacancies; Third, weigh 200 mg of the oxygen vacancy-loaded nickel-loaded indium oxide carrier prepared in step two, disperse it uniformly in a mixed solution composed of 30 mL of deionized water and 30 mL of ethanol, and ultrasonically treat it for 10 min to form a uniform suspension; add 1 g / L of ruthenium trichloride solution to the above suspension; Under continuous magnetic stirring, the mixed solution is irradiated with a 300 W xenon lamp for 1 h; after the reaction is completed, the solid product is collected by filtration, washed with deionized water three times, and finally dried at 70℃ overnight to obtain the final target catalyst, nickel-indium double-atom-loaded indium oxide with oxygen vacancies.

4. The Ni-Ru bimetallic supported oxygen-vacancy-rich indium oxide photocatalytic material for reduction of carbon dioxide to carbon monoxide according to claim 1 and the method of preparation thereof, characterized in that, The nickel-ruthenium bimetallic loading provides a synergistic active site, the loading of nickel enhances the adsorption of carbon dioxide, the loading of ruthenium provides hydrogen overflow, reduces the energy barrier of formic acid intermediates, and the increase of oxygen vacancies realizes the absorption of the full visible light spectrum of 200-1000 nm; by introducing nickel (Ni) and ruthenium (Ru) bimetallic and oxygen vacancies, the CO2 adsorption, hydrogen transfer reaction kinetics and light absorption capacity are respectively strengthened, and the three synergistic effects together improve the photocatalytic performance of efficiently converting CO2 into CO.

5. The preparation method according to claim 1, characterized in that, In step one, the hydrated indium nitrate is 0.1 mmol In(NO3)3·xH2O, and the nickel nitrate hexahydrate is 0.1 mmol Ni(NO3)2·6H2O; the ratio of 0.1 mmol of hydrated indium nitrate and 0.1 mmol of nickel nitrate hexahydrate is to provide a specific and equal metal molar ratio (In:Ni = 1:1) for the final material, which is the basis for building a bimetallic synergistic effect.

6. The method of claim 1, wherein, In step one, 0.1 mol of urea is added to adjust the solution to be alkaline, pH = 9; 0.1 mol of urea is added and hydrolyzed in the reaction, the purpose is to create a basic environment with pH = 9, which is a key step to induce precursor coprecipitation and form a specific microstructure (such as hydroxide or basic salt).

7. The preparation method according to claim 1, characterized in that, In step one and step two, the drying is carried out in a vacuum drying oven at 70℃, and the drying time is 12 h; 70℃ vacuum drying for 12 hours is to completely remove the water in the material under mild and uniform conditions, avoid the structure being destroyed during subsequent high temperature treatment, and ensure the reproducibility between batches.

8. The method of claim 1, wherein, In step two, the reduction process is carried out in a tube furnace, and the temperature is programmed to rise to 350℃ at a rate of 5℃ / min; the temperature is programmed to rise to 350℃ at a rate of 5℃ / min in the tube furnace, the purpose is to control the thermal decomposition process of the precursor, to gently produce a large number of oxygen vacancies while forming crystalline indium oxide, rather than excessive crystallization, so as to optimize the defect structure of the material.

9. The method of claim 1, wherein, In step three, the ruthenium source is a ruthenium trichloride solution with a concentration of 1 g / L; using a 1 g / L concentration of ruthenium trichloride (RuCl3) solution can accurately control the loading amount of noble metal ruthenium, and ensure that the high dispersion of nanoparticles is formed on the surface of the material by the photodeposition method.

10. The method of claim 1, wherein, In step three, the ultrasonic treatment time is 10 min; the ultrasonic treatment is carried out for 10 min, which aims to make the calcined powder fully dispersed in the solution to form a uniform suspension, so as to ensure that the ruthenium species can be uniformly deposited on the surface of the carrier, and avoid uneven loading caused by agglomeration.